2006
DOI: 10.1080/08941930600778230
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and Postoperative Administration of Hyperbaric Oxygen Improves Biochemical and Mechanical Parameters on Ischemic and Normal Colonic Anastomoses

Abstract: Colonic anastomotic leaks are a major postoperative complication, causing increased mortality and morbidity. Tissue ischemia is one of the most important factors that disrupt anastomotic healing. It is possible to reverse inadequate tissue oxygenation by using increased atmospheric pressure and hyperoxia, which are obtained from hyperbaric oxygen treatment (HBO). Our aim was to investigate the effects of preoperative and postoperative HBO treatment on normal and ischemic colonic anastomoses in rats. Eighty mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 41 publications
1
20
0
3
Order By: Relevance
“…Yagci et al 18 , used hyperbaric oxygen pre and postsurgically in normal and ischemic colic anastomoses in rats and the concluded that HBO increased the mechanical parameters in ischemic anastomosis, but the increasing in the values of pression of explosion in normal anastomosis was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yagci et al 18 , used hyperbaric oxygen pre and postsurgically in normal and ischemic colic anastomoses in rats and the concluded that HBO increased the mechanical parameters in ischemic anastomosis, but the increasing in the values of pression of explosion in normal anastomosis was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…As the surgical techniques and the suture materials, other factors interfere in anastomosis quality, as antibiotics 4,5 , antioxidants 6,7 , antineoplasics 8 , imunossupressors 9 , hormones 10 , trauma 11 , shock [12][13][14] , adherences 15,16 and ischemia 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…The literature lists several publications on the negative effects of poorly oxygenated tissue on healing 4,13 . Nevertheless, few studies have assessed the effect of an increased oxygen uptake to digestive tract anastomotic healing [9][10] . The mechanical parameters adopted to assess digestive anastomotic healing are tests that determine the intrinsic resistance of sutures as a surrogate of tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…Despite progress in surgical techniques and in the development of suture materials, dehiscence are still observed leading to reoperations, prolonged hospital stays, considerable costs, and higher morbidity and mortality rates 10 . Healing is a multifactoral process, the success of which depends on several local and systemic aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation